Showing Up: Disparities in Chronic Absenteeism between Students with and without Disabilities in Traditional Public Schools. Issue 8 (August 2019) - Gottfried, Michael A.; Stiefel, Leanna; Schwartz, Amy Ellen; Hopkins, Bryant
Background: While chronic absenteeism hurts all students, one particularly vulnerable group, students with disabilities (SWDs), has received little attention in research or policy. Particularly troubling is the dearth of research into the patterns of absences for SWDs and GENs who attend school together in urban school systems, given relatively higher absenteeism when compared to suburban and rural districts. Research Questions: First, how do rates of chronic absenteeism compare between SWDs and students without disabilities (GENs) attending the same schools (hereafter traditional schools)? Second, are there differences between SWDs who are educated in "GEN-majority" classrooms and those educated in "SWD-majority" classrooms? Finally, do these patterns differ for students with different disabilities? Subjects: Our study consists of GENs and SWDs in grades 1–6 who attended a traditional NYC public school between 2006 and 2012. Our sample includes 653, 736 students across 37, 867 classrooms, and 1, 148 public elementary schools. Measures include race/ethnicity, gender, age, foreign-born status, limited English proficiency, free/reduced price lunch eligibility, grade level, classroom ID, school ID, the number of days each student was absent, and the total number of school days each student was registered in the district. For SWDs, the data include indicators for the thirteen disability classifications defined under IDEA and a primary assigned special education setting. Research Design: We begin with a baseline model, where being chronically absent (i.e., missing 10% or more of the school year) is regressed on an indicator for being a SWD, controlling for grade and year. We build on this model by first including demographic control variables, then school fixed effects, and finally classroom fixed effects. We then explore this model for differences by type of classroom setting as well as by type of disability. Findings: Chronic absenteeism is considerably higher for SWDs than GENs in traditional schools, and there is important heterogeneity by disability classifications. Specifically, students with emotional disturbances exhibit extremely high rates of chronic absenteeism and the largest group of SWDs, students with learning disabilities, have quite high rates as well. Further, SWDs in GEN-majority classrooms are less likely to be chronically absent than those in SWD-majority classrooms, again with variation by disability. Conclusions: As the nationwide trend of providing SWDs with more education in GEN-majority classrooms continues to press forward, our study shows that increasingly GEN-majority settings are associated with fewer absences for SWDs. And while school attendance, among other non-achievement outcomes, are not the primary focus of IDEA, our findings point to how some school settings might be beneficial to some but put others at risk.